Resuspension of DNA Sequencing Reaction Products in Agarose Increases Sequence Quality on an Automated Sequencer. (September 2002) - Vatcher, G.; Smailus, D.; Krzywinski, M.; Guin, R.; Stott, J.; Tsai, M.; Chan, S.; Pandoh, P.; Yang, G.; Asano, J.; Olson, T.; Prabhu, A.-L.; et al.
We are investigating approaches to increase DNA sequencing quality. Since a major factor in sequence generation is the cost of reagents and sample preparations, we have developed and optimized methods to sequence directly plasmid DNA isolated from alkaline lysis preparations. These methods remove the costly PCR and postsequencing purification steps but can result in low sequence quality when using standard resuspension protocols on some sequencing platforms. This work outlines a simple, robust, and inexpensive resuspension protocol for DNA sequencing to correct this shortcoming. Resuspending the sequenced products in agarose before electrophoresis results in a substantial and reproducible increase in sequence quality and read length over resuspension in deionized water and has allowed us to use the aforementioned sample preparation methods to cut considerably the overall sequencing costs without sacrificing sequence quality. We demonstrate that resuspension of unpurified sequence products generated from template DNA isolated by a modified alkaline lysis technique in low concentrations of agarose yields a 384% improvement in sequence quality compared to resuspension in deionized water. Utilizing this protocol, we have produced more than 74 000 high-quality, long-read-length sequences from plasmid DNA template on the MegaBACE TM 1000 platform.